Mission design for interplanetary and lunar missions using electric propulsion - Chen, Zeng Yao (Nanyang Technological University, 2022)
Humans have come a long way in space voyage, over the year the industry had many breakthroughs since the first satellite launch in 1957. Today, we human have gotten so good in reducing the size of our technology that almost all humans can walk around with microcomputers right in our pockets. As such there is not limitation where this technology can be advantages in space voyage. Enter CubeSat a micro satellite the size similar to a toaster. These micro satellites can do a plethora of things, such as for research purposes, space exploration etc. These satellites have become popular among the education sector due to the low cost and easy to produce nature. Interplanetary travel is and always will be the next step for humans to perfect in space voyage. However, launching these CubeSats into space still costs a fortune which is not accessible to every researcher or country. Hence, to solve the monetary issue, Ansys Government Initiative (AGI)’s System Tool Kit (STK) can help researchers and space explorers alike to do simulated space travel at a relatively low cost. It can even be free if it is used for education purposes. In this project, the research will be conducted using the Astrogator module from STK to do simulated interplanetary trajectories with a satellite and calculate the delta V required in the process. Using the results of the simulation, research will be conducted to search the commercial market of a suitable propulsion unit that meets the requirements that can achieve this simulated mission.